Analisis Tingkat Produktivitas Petani Padi di Kelurahan Simarimbun - Poltak Pardamean Simarmata; Muhammad Yunus; Putra Arys Arianto Manurung (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2019)
This study aims to (1) know the factors that affect the productivity of wet land paddy farming in Siantar Marimbunsub-district of Kelurahan Simarimbun Regency (2) know the optimal using level of production factors in rice farming in Siantar Marimbunsub-district, Kelurahan Simarimbun regency. The analytical method used to analyze the factors that influence productivity is Multiple Linear Regression Analysis, and to determine the optimal level of use of production factors used NPM approach. Based on the result of research, it is found that (1) the use of Labor production factor (X1), Seed (X2), Urea Fertilizer (X3),Sp36 Fertilizer (X4), KCl Fertilizer (X5), Pesticide (X6) and Dummy influenced 84,42% productivity of rice paddy that shown by the coefficient of determination (R2) of 0.8442 while the remaining 15.58% influenced by other factors not described in this study. Regression results partially obtained that the use of labor production factor (X1) did not significantly affect productivity while the use of seed production factors (X2), fertilizer (X3), and pesticide (X4) had a significant effect on the productivity of wetland rice farming. (2) The use of wetland paddy production in Siantar Marimbunsub district had not been optimally seen from the result of NPM / Px was not the same as one so it is necessary to increase and decrease the use of production input. The optimal use of production factor for labor was 110 HOK, 60,24 Kg of seed, Urea fertilizer equal to 150 Kg, Sp36 fertilizer equal to 70 Kg, KCl fertilizer equal to 67 Kg and pesticide equal to 128,68 ml